Sejarah Mebel Ukir Jepara - Nangoy, Oktavianus Marti; Sofiana, Yunida (Humaniora, 2013)
Since 19th century, Jepara has been wellknown for furniture and craftings. It is shown by the appcreciation from some people claiming Jepara as an intregrated region for furniture and craftings. In Jepara, making furniture and craftings activities have become ingrained part of culture, arts, economic, social and politic. It is difficult to seperate them from its history, as it is not clear the time and place of making furniture and craftings. Thus, tracking the history is necessary to do, to know the development of Jepara as an integrated region for furniture and craftings nowadays.